Finite-time synchronization of delayed complex dynamical networks via sampled-data controller - Haripriya, M.; Manivannan, A.; Dhanasekar, S.; Lakshmanan, S. (Mathematical modelling and control, 2025)
This paper focused on the finite-time synchronization problem of complex dynamical networks (CDNs) with time-varying delay under sampled-data control schemes. A pinning control approach based on sampled-data was designed to achieve synchronization criteria. Developing a new looped Lyapunov functional with delayed information and sampling instants yielded sufficient conditions as linear matrix inequalities. The suggested CDNs were synchronized with one another since the derived criteria guaranteed the error CDN's asymptotic stability. A numerical example and corresponding simulation results confirmed the proposed control scheme's effectiveness.